IMPLEMENTASI METODE AHP-WP PADA SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN GURU TELADAN (Studi Kasus: Yayasan Abadiyah Kuryokalangan) - Rifan, Slamet; Arini, Florentina Yuni; Alamsyah, Alamsyah (Unnes Journal of Mathematics, 2016)
This research proposed an application of MADM (Multi Attribute Decision Making) in the problems of the exemplary teacher selection with assessment criteria: the preparation of teaching material, lesson plan, application of learning, mastery of the learning material, the use of learning resource/media and the discipline in teaching. In this research, AHP (Analytical Hierarchy Process) method’s was used for weighting the criteria and testing the consistency toward pairwise comparison matrix. If the matrix has been consistent then it can be continued to WP (Weighted Product) method’s process in implementing rank to determine the best alternative. The methods of this research include preliminary studies, data collection phase, system development phase and conclusion. From the results of the ranking in this system, it was found that the teacher got the highest score was teacher with code of teacher: A05 with score 0.0195981, so that the teacher was a recommendation teacher that was selected as an exemplary teacher.